Synthesis, structure, and antioxidant activity of anabasinium O,O-dimethylthiophosphate; Russian Journal of General Chemistry; Vol. 86, iss. 7 - Kabieva S. K.; Nurkenov O. A.; Seilkhanov T. M.; Bakibaev A. A. Abdigali Abdimanapovich; Gazaliev A. M. Arstan Maulenovich; Takibaeva A. T.; Voronova O. A. Olesya Aleksandrovna; Plotnikov E. V. Evgeny Vladimirovich (2016, 2016)
Title screen